Implementation of Collaborative Policy for Tourism Village Development in Bintan Regency, Riau Islands Province - Ambiya, Mohd. Zamir (Journal of Social Science, 2024)
This study was conducted to determine the Implementation of Collaborative Policy for Tourism Village Development in Bintan Regency, Riau Islands Province. Tourism has experienced a very rapid development so that the demand for varied tourist objects and destinations is getting higher, the presence of tourist villages is one of the answers to these needs. The role of the government and related stakeholders is becoming increasingly important in collaborating to respond to these developments. This research is designed descriptively - qualitatively. To see the Policy Implementation of Bintan Regent Regulation No. 31 of 2022 concerning tourist villages and villages, researchers used Ryan Nugroho's Policy Implementation Theory (2004: 159) and Emerson, Nabatchi and Ballough's Collaboration Theory (2012). This research was conducted in the tourist village of Bintan Regency, Riau Islands Province. The results showed that the implementation of the collaborative tourism village development policy in Bintan Regency has not been effective. This is due to the low proactivity of collaboration elements. To address this challenge, the research designed a collaboration model called the "POROS 1X-5Y in 5W-1H MODEL," which offers a systematic approach to improving the effectiveness of collaboration. Based on the findings, the implementation of collaboration policies still requires strengthening collaborative aspects in order to optimally support the development of tourist villages. The designed model is expected to be a strategic reference in the management and development of tourist villages in the future.